(3eOi GHGMI GdYed GdWHi hGdLQGMi Ydi LSe GdGfSGf (B/ s - (3YGOd SjO SjO TheGfs; (3GMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3jYJHQ gPG GdehVhY ef GdehVhYGJ GdLOjOI aj YGde GdWH abO COj GdJWhQ GdYdej hGdWHj efP YTQGJ GdSfjf Edi GSJYeGd CYVGA ef GdLSO GdEfSGfj hPdc dCZQGV YdGLjI aj MGdI Jhba HYV GdCYVGA GdMjI YfO GdeQjV aJe fbd Gdcdj hGdbdH hGdQFg hGdcHO Edj GdeQVj hbO fLMJ GNjQG YedjGJ fbd GdHfcQjGS hRQY GdCYVGA Yed YdGLj HdG LOGd HGdfSHI def jfbd Edjg GdYVh GdefRhY CjG cGf UGMH gPG GdCNjQ ShGA cGf TNUG MjG Ch ejJG cGf bO ChUj HGdJHQY HCYVGFg HYO haGJg CeG ef fRY efg GdYVh aj MjGJg adGjecf Gdbhd aj TCfg HCf GdWHjH jeGQS YedG YdGLjG ceG jJYPQ Gdbhd jGdEHGMI GSJfGOG Edi QVG GdeQjV s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdYed GdWHi hGdLQGMis; (3LSe GdGfSGfs; (3LSe GdGfSGfs; (3eSFhdjI GdWHjHs; (3NWC GdWHjHs; (3RQGYI GdCYVGAs; (3fbd GdCYVGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs